Social work research with marginalized groups – navigating an ethical minefield. Issue 1 (2nd January 2022) - Müller, Maja; Olesen, Annette; Rømer, Mette
ABSTRACT: This article considers ethics in practice in social work research involving marginalized groups. Based on fieldwork experiences in four qualitative empirical studies of marginalized groups, the article identifies ethical dilemmas that arose during the research process. Through a cross-case analysis of the ethical dilemmas, the article points out how these were associated with the vulnerable positions of the research participants and trust-building during the entire research process. The analysis embraces three ethical challenging stages of trust: 1) building and gaining trust, 2) trust, unintended situations and unwanted insight, and 3) leaving the field but staying in touch. In each stage the article illustrates how the ethical codes were practised and discuss how and why they were not enough to rely on in ethic in practice. The examples show how the researchers during the process had to supply the codes with on-the-spot ethical decisions taking the vulnerability and social position of the participants in consideration. The article points out how navigating in and around the marginalized group's vulnerability is an important approach to ethics in practice. It further concludes that ethic in practice is a relational and negotiated practice between the researcher and participant, where the participant influence how and when the researcher, for instance, leaves the field. By illustrating and discussing the researcher's experiences with ethics in practice the article contributes to a focus on ethical awareness and offers reflections from practice on how to navigate the ethical minefield of researching marginalized groups